Increasing The Activeness and Learning Achievement of Fourth Grade Students in Science Subjects Through Cooperative Learning Model at SDN Brebeg 01 - Ruswanto Ruswanto; Ana Andriani (UM Purwokerto Press, 2023)
Low student activeness and learning achievement are the background of the problem. The goal is to improve student activeness and learning achievement. This research uses the Classroom Action Research method. The research subjects were fourth grade students totaling 34 students, consisting of 17 male students, and 17 female students. Data collection techniques are observation, documentation, and tests. This research consisted of two cycles. Each cycle consists of two meetings and four stages, namely planning, action, observation and reflection. The research was conducted in September 2021. The application of the Think Pair Share type of Cooperative Learning model can increase activity and improve science learning achievement more than using the lecture and question and answer method. The data shows that in the pre-cycle student activeness was only 10 students, 8 students completed learning and the class average was 58.2 and in cycle 1 it increased to 24 active students, 22 students completed learning and the class average was 72.1. In Cycle 2, there were 34 active students, student 32 completions, and a class average of 82.9.